Clinical features of Malaysian children hospitalized with community-acquired seasonal influenza - Sam, I.C.; Abdul-Murad, A.; Karunakaran, R.; Rampal, S.; Chan, Y.F.; Nathan, A.M.; Ariffin, H. (2010)
Objectives: The clinical impact of seasonal influenza is understudied in tropical countries. The aim of this study was to describe the clinical features and seasonal pattern of influenza in children hospitalized in Malaysia, and to identify predictors of severe disease. Methods: Children hospitalized with community-acquired, laboratory-confirmed influenza at a teaching hospital in Kuala Lumpur, Malaysia during 2002-2007 were identified retrospectively. Clinical data were collected, and predictors of severe disease were identified by multivariate logistic regression. All influenza cases from 1982 to 2007 were also analyzed for seasonal patterns. Results: A total of 132 children were included in the study, 48 (36.4) of whom had underlying medical conditions. The mean age was 2.5 years and 116 (87.9) were < 5 years old. The most common presenting features were fever or history of fever, cough, rhinitis, vomiting, and pharyngitis. Severe influenza was seen in 16 patients (12.1; nine previously healthy), including 12 (9.1; eight previously healthy) requiring intensive care. There were three (2.3) deaths. Severe disease was associated with age < 12 months, female sex, and absence of rhinitis on admission. Influenza was seen year-round, with peaks in November-January and May-July. Conclusions: Seasonal influenza has a considerable impact on children hospitalized in Malaysia, in both the healthy and those with underlying medical conditions. (C) 2010 International Society for Infectious Diseases. Published by Elsevier Ltd. All rights reserved.